If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying solve + -5(2x + -11) = (2x + -3) + -11 Reorder the terms: elosv + -5(-11 + 2x) = (2x + -3) + -11 elosv + (-11 * -5 + 2x * -5) = (2x + -3) + -11 elosv + (55 + -10x) = (2x + -3) + -11 Reorder the terms: 55 + elosv + -10x = (2x + -3) + -11 Reorder the terms: 55 + elosv + -10x = (-3 + 2x) + -11 Remove parenthesis around (-3 + 2x) 55 + elosv + -10x = -3 + 2x + -11 Reorder the terms: 55 + elosv + -10x = -3 + -11 + 2x Combine like terms: -3 + -11 = -14 55 + elosv + -10x = -14 + 2x Solving 55 + elosv + -10x = -14 + 2x Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-55' to each side of the equation. 55 + elosv + -55 + -10x = -14 + -55 + 2x Reorder the terms: 55 + -55 + elosv + -10x = -14 + -55 + 2x Combine like terms: 55 + -55 = 0 0 + elosv + -10x = -14 + -55 + 2x elosv + -10x = -14 + -55 + 2x Combine like terms: -14 + -55 = -69 elosv + -10x = -69 + 2x Add '10x' to each side of the equation. elosv + -10x + 10x = -69 + 2x + 10x Combine like terms: -10x + 10x = 0 elosv + 0 = -69 + 2x + 10x elosv = -69 + 2x + 10x Combine like terms: 2x + 10x = 12x elosv = -69 + 12x Divide each side by 'losv'. e = -69l-1o-1s-1v-1 + 12l-1o-1s-1v-1x Simplifying e = -69l-1o-1s-1v-1 + 12l-1o-1s-1v-1x
| 300-16t^2=0 | | 3n-2+2(2n+1)=6n+7 | | 6+5x=2.666 | | 264=8(-5a-7) | | 9+9=180 | | -8(6b+6)=-96 | | 3(x+10)-2(-x+10)=10 | | 27/16-8/9= | | -6c+q=-9c+7 | | 81=-3(5-8b) | | 45+2.50=9.25 | | 6.5x+7=1.5x+32 | | -4+6x=-.375 | | 5(x+8)+3(-x+8)=-2 | | 1/30x=1/40x | | -357=-7(-7x+2) | | -7n-4(6-4n)=-39+4n | | 20=500-60m | | -5(8m-4)=260 | | 8+.4x=4.4 | | 100=2(2+6k) | | 2+5y-y=y-2+25 | | 86=2(8m-5) | | 3(x+14)+4(x+7)=-35 | | 8-4v=-5(v+4)+5v | | 206=x+7x | | 206=x+(x+7) | | -18+2x=8(6x-8) | | 60=10x+10 | | 3x+2(3x+1)=11 | | 49/70=x/100 | | 15.83=5.95p |